Perancangan Interior Galeri Kebaya Modern di Surabaya - Winnie Tritanjaya Wong; Lintu Tulistyantoro (Intra, 2014)
Kebaya means an upper dress which was used firstly by Indonesian women, especially Javanese women. Nowadays, kebaya has transformed into much more modern design soit is desired by the Indonesian society.To support those people, will be held a modern kebaya gallery with many facilities such as:lobby, fashion show area,exhibition,store,consultation room,and many more.